Plantiness: Re-evaluating plant human relationships across temporal landscapes in Britain - Masterson, MJ (2024)
‘Plantiness’ explores the notion that plants are lively, active beings with the ability to shape and change us as we have also done to them. This theory of reciprocity considers plant intelligence and plant materiality, while incorporating ideas of making-in-growing, aesthetics, labour, and edibility. This provides a framework for approaching plant-human relationships in a way that is accessible to those outside of plant studies/sciences. With the help of a range of disciplines — including plant biology, ethnobotany, critical plant studies, and archaeobotany — plantiness can expand the vegetal world and encourage us to consider the ‘planty’ perspective within archaeology.